The Effect of Grab Start On Some Biomechanical Variables - Abd, Abe Ramz (Journal of Physical Education, 2018)
The Effect of Grab Start On Some Biomechanical VariablesThe research aimed at identifying the values of some biomechanical variables during the grab start in swimming. The problem of the research lies in finding the best position that the swimmer gives the best strength and effort as well as identifying the differences between the two positions. The researcher used the descriptive method. The subjects were (5) Iraqi advance swimmers. All variables were selected carefully then the data was collected and treated using proper statistical operations. The researcher concluded significant statistical differences between the values of some biomechanical variables of the grab start. Finally the researcher recommended the necessity of coaches paying attention to this type of start in swimming to achieve better results in speed and kinetical variables.